The secret of vigor : how to overcome burnout, restore metabolic balance and reclaim your natural energy - Talbott, Shawn M. (Hunter House, 2012)
"The Secret of Vigor: How to Overcome Burnout, Restore Metabolic Balance, and Reclaim Your Natural Energy is a proven and powerful, cutting-edge, 7-day program that can counter the effects of chronic stress to help people: - restore balance in the body - improve mental/physical energy - reduce fatigue - alleviate depression - sharpen mental focus - lose weight - manage their risk of diabetes, cancer and heart disease"--